The Effectiveness Of Article 412 Of The New Criminal Code In Combating The Practice Of Cohabitation In Medan City - Delviani Damanik; Rajin Sitepu (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
Cohabitation practices (locally known as cohabitation) have long been a social phenomenon that attracts public attention in Indonesia because they are considered contrary to religious norms, decency, and the moral values upheld by society. Prior to criminalization, various non-penal measures such as moral and religious guidance, family education, social supervision, and legal counseling had been implemented to address the practice. However, these efforts were considered insufficient to effectively prevent cohabitation, leading lawmakers to regulate cohabitation as a criminal offense through Article 412 of Law Number 1 of 2023 concerning the Criminal Code. The criminalization was based on the view that cohabitation constitutes conduct that is harmful, or at least contrary to the values embraced by society, thereby requiring the intervention of criminal law as a measure of last resort (ultimum remedium). Nevertheless, the effectiveness of the implementation of Article 412 remains a matter of debate because the offense of cohabitation is categorized as a complaint-based offense (delik aduan), which can only be prosecuted upon a complaint by certain authorized parties. This study aims to analyze the regulation of the criminal offense of cohabitation under the New Criminal Code and to assess the effectiveness of Article 412 in addressing cohabitation practices on Gatot Subroto Street, Sei Putih Timur II Subdistrict, Medan Petisah District, Medan City. The research employed an empirical legal method with a socio-juridical approach. Data were collected through interviews and library research and were analyzed qualitatively. The findings indicate that Article 412 has provided a clear legal basis for addressing cohabitation practices; however, its implementation has not yet been effective. The main obstacles include the complaint-based nature of the offense, the low number of complaints submitted, the limited public understanding of the applicable legal provisions, and the continued existence of cohabitation practices within the community. Therefore, greater legal awareness campaigns, stronger community involvement, and an evaluation of the complaint mechanism are necessary to ensure that the objectives of criminalizing cohabitation can be achieved more effectively.